Effects of hypoxia, hyperoxia, and hypercapnia on baseline and stimulus-evoked BOLD, CBF, and CMRO(2) in spontaneously breathing animals - Sicard, Kenneth M. (2005)
Functional magnetic resonance imaging (fMRI) was used to investigate the effects of inspired hypoxic, hyperoxic, and hypercapnic gases on baseline and stimulus-evoked changes in blood oxygenation level-dependent (BOLD) signals, cerebral blood flow (CBF), and the cerebral metabolic rate of oxygen (CMRO(2)) in spontaneously breathing rats under isoflurane anesthesia. Each animal was subjected to a baseline period of six inspired gas conditions (9% O(2), 12% O(2), 21% O(2), 100% O(2), 5% CO(2), and 10% CO(2)) followed by a superimposed period of forepaw stimulation. Significant stimulus-evoked fMRI responses were found in the primary somatosensory cortices. Relative fMRI responses to forepaw stimulation varied across gas conditions and were dependent on baseline physiology, whereas absolute fMRI responses were similar across moderate gas conditions (12% O(2), 21% O(2) 100% O(2), and 5% CO(2)) and were relatively independent of baseline physiology. Consistent with data obtained using well-established techniques, baseline and stimulus-evoked CMRO(2) were invariant across moderate physiological perturbations thereby supporting a CMRO(2)-fMRI technique for non-invasive CMRO(2) measurement. However, under 9% O(2) and 10% CO(2), stimulus-evoked CBF and BOLD were substantially reduced and the CMRO(2) formalism appeared invalid, likely due to attenuated neurovascular coupling and/or a failure of the model under extreme physiological perturbations. These findings demonstrate that absolute fMRI measurements help distinguish neural from non-neural contributions to the fMRI signals and may lend a more accurate measure of brain activity during states of altered basal physiology. Moreover, since numerous pharmacologic agents, pathophysiological states, and psychiatric conditions alter baseline physiology independent of neural activity, these results have implications for neuroimaging studies using relative fMRI changes to map brain activity.